Local Population structure in Arabian Peninsula revealed by Y-STR diversity - Alshamali, F (2009)
Genetic studies have been underway on Arabian Peninsula populations because of their pivotal geographic location for population migration and times of occurrence. To assist in better understanding population dynamics in this region, evidence is presented herein on local population structure in the Arabian Peninsula, based on Y-STR characterisation in four Arabian samples and its comparison in a broad geographical scale. Our results demonstrate that geography played an important role in shaping the genetic structure of the region around the Near-East. Populations are grouped regionally but none of these groups is significantly differentiated from others and all groups merge in the Near-East, in keeping with this important migration corridor for the human species. Focusing on the Arabian Peninsula, we show that Dubai and Oman share genetic affinities with other Near-Eastern populations, while Saudi Arabia and Yemen show a relative distinctive isolated background. Those two populations may have been kept relatively separated from migration routes, maybe due to their location in a desert area.